2021
DOI: 10.2147/ijgm.s324164
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Analysis of Iron-Deficiency Anemia Complicated by Splenomegaly

Abstract: Objective: This study aimed to determine the incidence of iron-deficiency anemia (IDA) complicated by splenomegaly in our hospital over the past 6 years and to analyze the possible causes of this result. Methods: This is a retrospective study. In total, 668 patients with IDA who were hospitalized in the hematology department of our hospital from 2013 to 2019 were selected as the research subjects and included in the IDA group, and 3201 patients who underwent outpatient physical examinations in our hospital dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Upon iron repletion, recovery from IDA has features of stress erythropoiesis, including rapid erythropoietic expansion and reticulocytosis. Splenomegaly is evidenced in mice ( Gibson et al, 2011 ) and patients ( Wei et al, 2021 ) with severe ID, consistent with extramedullary hematopoiesis.…”
Section: Introductionmentioning
confidence: 74%
“…Upon iron repletion, recovery from IDA has features of stress erythropoiesis, including rapid erythropoietic expansion and reticulocytosis. Splenomegaly is evidenced in mice ( Gibson et al, 2011 ) and patients ( Wei et al, 2021 ) with severe ID, consistent with extramedullary hematopoiesis.…”
Section: Introductionmentioning
confidence: 74%
“…Accordingly, in cases of compensatory hematopoiesis outside the bone marrow, an enlarged splenic mass was frequently observed. 62,63 Our supplementation studies revealed that curcumin and BPA treatment also caused a notable decline of the F I G U R E 8 Curcumin treatment altered the polyamine pattern and the expression of genes involved in spermidine production in murine spleen tissue. Tissues derived from a former 0.2% curcumin supplementation mice study 24 were analyzed for (A) their polyamine content and (B) their transcript levels of related key genes.…”
Section: Discussionmentioning
confidence: 91%
“…However, recent studies suggest that under certain pathological conditions including iron‐deficiency anemia the spleen can be stimulated to restore hematopoietic function. Accordingly, in cases of compensatory hematopoiesis outside the bone marrow, an enlarged splenic mass was frequently observed 62,63 …”
Section: Discussionmentioning
confidence: 99%
“…An abnormal blood hemoglobin level is one of the causes of the most severe health crises, such as strokes (Al-Harbi et al, 2020;Chang et al, 2020;Guo et al, 2019;Naess et al, 2019;Yoshimura et al, 2020), severe cognitive impairment after a stroke (He et al, 2020), cardiovascular disorders and diseases and heart attacks (Houghton et al, 2020;Park et al, 2020;Rocha et al, 2018;Sabah et al, 2020;Zhang et al, 2019), Alzheimer's and dementia risks and cognitive impairment (Kim et al, 2019;Kung et al, 2021;Shah et al, 2011;Wolters et al, 2019), blood clots (Faes et al, 2019;Gupta et al, 2019), blood diseases, such as sarcopenia leukemia (Hamamyh, and Yassin, 2020;Yoshimura et al, 2020), splenomegaly (Li et al, 2019;Majer et al, 2021;Wei et al, 2021), deterioration of kidney functions (Tsujita et al, 2019), thyroid disorders (Ahmed et al, 2021;Ghiya, and Ahmad, 2019;Islam et al, 2021), blood pressure disorders (ZHAO et al, 2023), dysphagia (Yoshimura et al, 2020), restless legs syndrome (Lyu et al, 2019;Olgun Yazar et al, 2019;Panvatvanich, and Lolekha, 2019), immunity disorders (Yang et al, 2019), risk of viral and bacterial infections, such as COVID-19 (Chowdhury, and Anwar, 2020), ulcers (Soodmand et al, 2019;Yammine et al, 2021), gout (Eun et al, 2019;…”
Section: Introductionmentioning
confidence: 99%